Extraction of Some Ellagic Tannins and Ellagic Acid from Oak Wood Chips (Quercus pyrenaica L.) in Model Wine Solutions: Effect of Time, pH, Temperature and Alcoholic Content - Jordão, A.M.; Ricardo-da-Silva, J.M.; Laureano, O. (South African Journal of Enology and Viticulture, 2017)
The subject of the present work is the study of the influence of pH, temperature, alcoholic content and time on the extraction of some individual ellagic tannins (castalagin, vescalagin, grandinin, roburin D and E) and ellagic acid from oak wood chips (Quercus pyrenaica L.) within model wine solutions. The determination of these compounds by reversed-phase high-performance liquid chromatography (HPLC), after 104 extraction days, enabled us to establish the qualitative and quantitative evolution of each component and the effect of each extraction condition on individual and total ellagic tannins from oak wood chips. Vescalagin and castalagin were the most abundant individual ellagic tannins measured under all extraction conditions. Individual ellagic tannins and ellagic acid increased during the first weeks of extraction, followed by a decrease. Under the extraction conditions examined, temperature was the main factor influencing ellagic tannins and elagic acid evolution. The results suggest that a decrease/degradation of these compounds is less noticeable at low temperatures (12ºC). After 104 extraction days the ellagic tannins content in a model wine solution at 12ºC was higher than the content of ellagic tannins in solutions at 20ºC. On the other hand, the effects of alcoholic content and pH of model wine solutions on the extraction and evolution of the analysed compounds (except for castalagin and vescalagin) seemed to be less important than temperature.